Ordinary disasters: On unexceptional flooding in LA's San Fernando Valley - RANDLE, Sayd (Institutional Knowledge at Singapore Management University, 2020)
Talking about flood as California's" other big one," otherwise known as a plausible natural disaster with the power to cause damage equivalent to that caused by a massive earthquake, does important work in capturing the imagination. Nearly a quarter submitted short stories about narrowly escaping death-by-ARkStorm, piling on the melodrama and watery metaphors. Because of its sheer scale, epic flooding is not hard to picture and/or to fear, even amidst the palm trees of Los Angeles.[...] I do fear that ignoring the more quotidian flare-ups and inundations and dry spells and snowstorms and other threats, the unevenly distributed" slow violence" that causes painful and sometimes fatal exposure, will allow a slew of dangerous environmental inequities to persist below the radar. Because as environmental justice activists have been reminding us for generations now, stop waiting for some damn event, the action is …